Middle-School "At-Risk" Student-Athletes and Proposition 42 - Jesudason, Melba (My University, 1990)
This paper will discuss the two propositions by the National Collegiate Athletic Association (NCAA) which are supposed to resolve the problems of recruiting undereducated and poor athletes who do not meet the academic requirements for college and university admission and fail to graduate after four years: first, Proposition 48 (P48), enacted in 1986, and second, Proposition 42 (P42), which will go into effect in August 1990. It described the issues raised by these propositions, which mostly concerned the black, poor, and minority group-athletes in Division I institutions only. Furthermore, it discussed the reasons why reachmg the middle school "at-risk" student-athlete could be the solution to the problems posed by P48 and P42, and suggested some ways of helping this group.
Keywords: race; demographics; at-risk; eligibility